A search for C-H···O type hydrogen bonds in Lamivudine (3TC). An exploratory conformational and electronic analysis - Fidanza, N. G. (2001)
A conformational study of the molecule Lamivudine (3TC), or cis-1-[2′-hydroxymethyl-5′-(1,3-oxathiolanyl)] cytosine, was carried out. Rotation about the C-N bond (φ1) and about the C-CH2(OH) bond (φ2), which connects the hydroxymethyl group to the five member ring, led to a conformational potential energy surface. The conformational potential energy 2D map, obtained at the HF/3-21G level of theory, had several minima. A topological analysis of the electron density was carried out on four selected ab initio minimum energy conformations, using judiciously constructed hartree-fock (RHF) wave functions. In order to see all possible hydrogen bonding, the DFT wave function was generated using a mixed basis set; a 6-311 + +G** basis was employed on atoms involved in hydrogen bonding interactions and a 3-21G basis on all other atoms. For this analysis the theory of atoms in molecules, developed by Bader, was used. The stability of the intramolecular hydrogen bonding interactions was analyzed in terms of the results obtained.